Pengaruh Kemandirian Belajar Terhadap Hasil Belajar Daring Mahasiswa Geografi Universitas Negeri Makassar - Ramli Umar; Sukri Nyompa; Fembriyanti Novela Sary (LaGeografia, 2022)
Online learning requires students to improve and have more independence in learning. They also take the initiative to seek, understand, and explore the learning materials themselves. With this theme, the researchers conducted descriptive quantitative research in order to find out the condition of learning independence of students in the Department of Geography, FMIPA UNM and what kind of effect it had on their learning outcomes. The population of this study were active students of the Department of Geography, FMIPA UNM class 2017-2020 for the 2020/2021 academic year. By determining the sample stratified random sampling using the Slovin formula. The research data was obtained through a questionnaire in the form of a google form that was distributed and processed using descriptive statistical analysis (SPSS) by displaying the results of the study using tables, graphs and percentages which were then described qualitatively. The results of this study state that the learning independence of students of the Department of Geography FMIPA UNM class 2017-2020 2021 has high learning independence, this can be seen from the results of the classification of learning independence of 61% or 53 students from 87 samples. And most of the learning outcomes get high learning outcomes seen from the presence of 60 or 69% of students. with the results of the f test obtained fcount = 4.499 > ftable = 3.95 with a value of sig.0.037 <0.05 means that there is a positive influence of learning independence on learning outcomes by 5% while the relationship between learning independence and learning outcomes is 0.224 (low).AbstrakPembelajaran daring menuntut mahasiswa untuk meningkatkan dan lebih memiliki kemandirian belajar. Juga berinisiatif mencari, memahami, dan mendalami sendiri materi pembelajaran. Dengan mengusung tema ini peneliti melakukan penelitian kuantitatif deskriptif guna mencari tahu kondisi kemandirian belajar mahasiswa Jurusan Geografi FMIPA UNM dan seperti apa pengaruhnya terhadap hasil belajar yang dicapainya. Populasi penelitian ini adalah mahasiswa aktif Jurusan Geografi FMIPA UNM angkatan 2017-2020 tahun ajaran 2020/2021. Dengan penentuan sampel stratified random sampling menggunakan rumus Slovin. Data penelitian diperoleh melalui angket dalam bentuk google form yang telah disebar dan pengolahannya menggunakan analisis statistik deskriptif (SPSS) dengan menampilan hasil penelitian menggunakan tabel, grafik dan persentase yang kemudian dideskripsikan secara kualitatif. Hasil penelitian ini menyatakan bahwa kemandirian belajar mahasiswa Jurusan Geografi FMIPA UNM angkatan 2017-2020 2021 memiliki kemandirian belajar yang tinggi, hal ini dilihat dari hasil klasifikasi kemandirian belajar sebesar 61% atau 53 mahasiswa dari 87 sampel. Dan hasil belajarnya sebagian besar mendapatkan hasil belajar yang tinggi dilihat dari adanya 60 atau 69% mahasiswa. dengan hasil uji f diperoleh fhitung=4.499 > ftabel=3.95 dengan nilai sig. 0,037 <0,05 berarti ada pengaruh positif kemandirian belajar terhadap hasil belajar sebesar 5% adapun hubungan kemandirian belajar dengan hasil belajar sebesar 0,224 (rendah).